A closer look: Comparing methods to measure methane emissions from sheep - Kariuki, Patrick; Gurmu, Endale Balcha; Slater, Annabel; Arndt, Claudia (International Livestock Research Institute, 2024)
Ruminant livestock produce enteric methane in their multi-chambered stomachs when they digest plant matter. Most methane is released through belching—contrary to a common misconception, only about 5% of livestock methane is produced through flatulence. Methane is a potent greenhouse gas (GHG) which significantly contributes to climate change. However, a recent survey in Ethiopia conducted by ILRI’s Mazingira Centre has highlighted a significant problem—different GHG measurement models are producing different values, leaving researchers uncertain as to which model is most accurate.